The Pengaruh Profitabilitas, Solvabilitas, dan Aktivitas terhadap Nilai Perusahaan dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Makanan dan Minuman Yang Terdaftar di Bei Tahun 2017-2022. - Wulandari, Niken Rara; Wardani, Laila (Postgraduate, University of Mataram, 2024)
This research aims to analyze the effect of profitability, leverage and activity on company value with company size as a moderating variable. This research is a causal associative research with a quantitative approach. In this research, sample selection was carried out using a purposive sampling method which focused on food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2017-2022 research period. By considering the established criteria, the sample was obtained from 28 companies from 46 companies so that the research data analyzed amounted to 168 observations. In this research, the panel data regression model is applied using the Fixed Effect Model (FEM) approach, while testing the moderating variables is carried out using Moderated Regression Analysis (MRA). The model data analysis utilizes the Eviews version 12 program. The research results show that profitability has a positive and significant effect on company value. Leverage has a positive and significant effect on company value, and activity has a positive and insignificant effect on company value. Company size is unable to moderate the influence of profitability, solvency and activity on company value